The Effectiveness of Group Counseling with Reinforcement Techniques to Increase Self-Efficacy - Maghfiroh, Siti Laylatul; Lianawati, Anyong; Farid, Dimas Ardika Miftah (Universitas Ahmad Dahlan, 2023)
This study aims to determine the effectiveness of group counseling with reinforcement techniques in improving self-efficacy of students at SMA Wachid Hasyim 5 Surabaya. This study uses the one group pre-test post-test design method. The sample used was 6 students who had the lowest self-efficacy from the pre-test results that had been conducted. This study is a quantitative study where the results obtained are reviewed from the results of the pre-test and post-test. The final results of the post-test scores given to 6 students showed an increase in self-efficacy scores, which initially one student was in the low category then changed to the high category, while the other 5 students were in the same category, namely the medium category when the post-test and pre-test but experienced changes in value. The results of the statistical test where Asymp. Sig (2-tailed) is worth 0.027 because 0.027 is less than 0.05, it can be said that Ha is accepted, this can be seen by comparing the significant score of 0.05. The provision of treatment using reinforcement techniques with group counseling shows the results of this study where there are changes that occur so that it can be concluded that group counseling with reinforcement techniques is effective in increasing the self-efficacy of students at SMA Wachid Hasyim 5 Surabaya.